Polyethylene and Polyvinyl Chloride-Blended Polystyrene Nanofibrous Sorbents and Their Application in the Removal of Various Oil Spills. (8th April 2020) - Alnaqbi, Mohamed. A.; Al Blooshi, Afra G.; Greish, Yaser E.
Abstract : Polymers provide a wide range of properties, and these properties can be greatly enhanced and modified through polymer blending. Polymer blending combines the properties and advantages of their original polymers. This paper showcases hydrophobic polymers prepared through polymer blending; these blends are characterized and evaluated for their efficiency in the removal of crude oil spills from aqueous media. The application of these blends holds a great deal of importance in preserving the environment and the recovery of lost oil in spills. The blends are produced using polystyrene (PS) as the matrix polymer and individually blending poly(vinyl chloride) (PVC) and polyethylene (PE) with the PS consisting of proportions of 5–20 wt.% each. The blends are then electrospun into bead-free microfibers with interconnected porosities as shown by their respective scanned electron micrographs. All fibrous sorbents showed a high affinity towards the removal of crude oil, motor oil, and diesel spills. The highly viscous motor spill showed a different pattern of sorption onto fibers than that of crude oil and diesel spills. Upon comparing all the studied electrospun fibers to commercially available polypropylene fibrous sorbents, results show that the sorption efficiency of the electrospun fibers is superior. Most notably, both PS-PE5 and PS-PVC5 fibers showed to be highly more effective than commercially available polypropylene (PP) sorbents towards all types of oil spills.